2018
DOI: 10.1007/s11060-018-2761-4
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced leukocytosis is associated with poor survival in newly diagnosed glioblastoma

Abstract: Despite its well-characterized side effects, dexamethasone is widely used in the pre-, peri- and postoperative neurosurgical setting due to its effective relief of tumor-induced symptoms through the reduction of tumor-associated edema. However, some patients show laboratory-defined dexamethasone induced elevation of white blood cell count, and its impact on glioblastoma progression is unknown. We retrospectively analyzed 113 patients with newly diagnosed glioblastoma to describe the incidence, risk factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 23 publications
0
41
1
2
Order By: Relevance
“…A possible implication of this finding is that edema may reduce the efficacy of TTField therapy, and might be considered as a predictor of non-response. However, this latter point will be difficult to test conclusively, given the known association between edema and poor outcomes [32], and the confounding nature of drugs which may reduce edema, but which themselves can be associated with poor outcomes [33]. Moreover, we found contrasting results when PLD was assessed.…”
Section: Discussionmentioning
confidence: 81%
“…A possible implication of this finding is that edema may reduce the efficacy of TTField therapy, and might be considered as a predictor of non-response. However, this latter point will be difficult to test conclusively, given the known association between edema and poor outcomes [32], and the confounding nature of drugs which may reduce edema, but which themselves can be associated with poor outcomes [33]. Moreover, we found contrasting results when PLD was assessed.…”
Section: Discussionmentioning
confidence: 81%
“…New effective therapeutic strategies are therefore needed to target the BBB dysfunction associated with meningitis [3]. The benefit of dexamethasone has also been questionable in cancer therapy as elaborated in our recent review [20], where it is used in edema management particularly in brain tumors [19,30,66]. Interestingly, one mechanism proposed for the action of dexamethasone on edema reduction in glioma was via downregulation of VEGF leading to reduced permeability; the efficacy of dexamethasone, however, was dramatically reduced during hypoxia [50].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the tumor reappeared after 1–4 weeks and was much more aggressive (Buxton et al, 1997; Zaki et al, 2004; Goh et al, 2009). It has also been observed that DEX therapy reduced the OS of a particular subgroup of GBM patients (Dubinski et al, 2018). In this study, 35 patients received preoperative DEX and compared to 78 control patients.…”
Section: Dex Therapy In Gbmmentioning
confidence: 98%